GE_GERICHTE A/1824/2020 vom 29. Mai 2013 - GE Cour de justice (2013)
DROIT D'ÊTRE ENTENDU;RÉNOVATION D'IMMEUBLE;REMISE EN L'ÉTAT;BAIL À LOYER;LOYER;RESTITUTION(EN GENERAL);DROIT PRIVÉ | LDTR.9; LDTR.10.al1; LDTR.12; LDTR.43; LDTR.44; LCI.129.lete; RGL.4.al3